2022
DOI: 10.1177/23259671221094788
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Anterior Cruciate Ligament Reconstruction in Patients Older Than 50 Years and Younger Than 30 Years

Abstract: Background: Few studies have compared the outcomes of anterior cruciate ligament (ACL) reconstruction between older patients and younger patients. Purpose: To evaluate the clinical and functional outcomes of ACL reconstruction with autologous hamstring tendon in patients >50 years and <30 years. It was hypothesized that the outcomes would be comparable between these age groups. Study Design: Cohort study; Level of evidence, 3. Methods: Patients >50 years (older group) or <30 years (younger group) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 27 publications
1
6
0
Order By: Relevance
“…Weng et al. 44 stated patients aged older than 50 years showed similar results with patients aged younger than 30 years and showed low complication rates as well at their cohort study.…”
Section: Discussionsupporting
confidence: 56%
“…Weng et al. 44 stated patients aged older than 50 years showed similar results with patients aged younger than 30 years and showed low complication rates as well at their cohort study.…”
Section: Discussionsupporting
confidence: 56%
“…The low revision rate found in the study patients may be attributed in part to the fact that older athletes typically participate in less intense sports and have overall lower activity level compared to high school or collegiate-aged patients. 40,41 Furthermore, older patients may not return to sports as early as their younger counterparts. 4 The processing of allograft tissue with the goal of reducing the risk of disease transmission and increasing the availability of allograft tissue has been extensively studied, and irradiation has been shown to have an important effect on graft failure.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have evaluated the benefit of ACLR in middle-aged patients and found outcomes comparable to those in younger patients [6,11,25,26,29,37]. Furthermore, some well-documented researches have demonstrated excellent clinical results following ACLR in selected and motivated patients older than 50 years [7,9,17,22,23,27,35,36]. In addition, few studies have reported that ACLR in active patients over 60 years without OA could restore knee stability and allow patients to return to preinjury activity levels [1,18,31,33].…”
Section: Introductionmentioning
confidence: 99%